Reactive dye adsorption onto a novel mesoporous carbon - Galán, José; Rodríguez Rodríguez, Araceli; Gómez Martín, José Mª; Allen, Stephen J.; Walker, Gavin M. (Elsevier, 2025)
A new mesoporous carbon (MCSG60) was developed using an inexpensive commercial mesoporous silica gel as a template and sucrose as the carbon source. The surface area, porosity and density of the carbon were determined. The material possesses a high specific surface area and pore volume accessible for most typical aqueous pollutants. The adsorbent material was tested in a batch dye adsorption system. The behaviour of three reactive dyes adsorbed onto MCSG60 was evaluated (Naphthol Blue Black, NBB; Reactive Black 5, RB5; and Remazol Brilliant Blue R, RBBR). The maximum adsorption capacities obtained for the dyes were: 270 mg/g for NBB; 270 mg/g for RB5; and 280 mg/g for RBBR. Kinetic studies indicated that the adsorption process onto the mesoporous carbon was rapid and that equilibrium was reached in less than 1 h for all the dye systems investigated. Further batch experiments showed MCSG60 successfully adsorbed the dyes over a wide pH range and at low adsorbate concentration. The adsorption potential of MCSG60 for dye removal was further evaluated using a fixed-bed adsorption column.